2023
DOI: 10.3389/fepid.2023.1095236
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease, associated risk factors, and risk of dementia: An umbrella review of meta-analyses

Abstract: IntroductionCardiovascular diseases (CVDs) have been associated with an increased risk of dementia; yet the evidence is mixed. This review critically appraises and synthesises current evidence exploring associations between dementia risk and CVD and their risk factors, including coronary heart disease, heart failure, atrial fibrillation, hypertension, hyperlipidaemia, and arterial stiffness.MethodsMEDLINE, Embase, PsycINFO, and the Cochrane Database of Systematic Reviews were searched to identify systematic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Importantly, an excess of high-fat protein intake, such as red meat, increases the risk of cardiovascular diseases and diabetes [ 46 ], an outcome not observed for poultry consumption [ 47 ]. This may explain why high consumption of red meat, in particular, is not associated with reduced dementia risk [ 48 ]. Additionally, preclinical studies indicate that diets high in saturated fat can heighten oxidative stress, neuroinflammation, and altered HN [ 49–52 ]—changes all associated with dementia [ 5 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, an excess of high-fat protein intake, such as red meat, increases the risk of cardiovascular diseases and diabetes [ 46 ], an outcome not observed for poultry consumption [ 47 ]. This may explain why high consumption of red meat, in particular, is not associated with reduced dementia risk [ 48 ]. Additionally, preclinical studies indicate that diets high in saturated fat can heighten oxidative stress, neuroinflammation, and altered HN [ 49–52 ]—changes all associated with dementia [ 5 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in blood lipids, adipose and muscle tissue distribution, blood pressure, heart rate, hand grip strength, and anthropometric measures such as body mass index (BMI) and waist‐to‐hip ratio are all associated with ageing (Massy‐Westropp et al, 2011 ; Mielke et al, 2010 ; Rodgers et al, 2019 ; Sebastiani et al, 2017 ). Despite these measures being classified as markers of normal body function rather than disease‐specific biomarkers, recent studies have highlighted their utility for risk detection and disease monitoring across cardiovascular disease and dementia (Brain et al, 2023 ). For example, research has suggested that dysregulation in lipid metabolism in Alzheimer's disease may predict cognitive decline (Wong et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in blood lipids, adipose and muscle tissue distribution, blood pressure, heart rate, hand grip strength, and anthropometric measures such as body mass index (BMI) and waist-to-hip ratio (WHR) are all associated with ageing (Massy-Westropp et al, 2011; Mielke et al, 2010; Rodgers et al, 2019; Sebastiani et al, 2017). Despite these measures being classified as markers of normal body function rather than disease-specific biomarkers, recent studies have highlighted their utility for risk detection and disease monitoring across cardiovascular disease and dementia (Brain et al, 2023). For example, research has suggested that dysregulation in lipid metabolism in Alzheimer’s disease may predict cognitive decline (Wong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these measures being classified as markers of normal body function rather than disease-specific biomarkers, recent studies have highlighted their utility for risk detection and disease monitoring across cardiovascular disease and dementia (Brain et al, 2023). For example, research has suggested that dysregulation in lipid metabolism in Alzheimer's disease may predict cognitive decline (Wong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%